KINERJA PETUGAS PENGURUS BARANG MILIK DAERAH DI RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN LANDAK - Ignasius Nico Agung Putra Pratama E.42009054 (FISIP Universitas Tanjungpura Pontianak, 2022)
This script aim to investigate the performance of the products management officer at the General Hospital of Landak Regency in implementing the regency's property records at the General Hospital of Landak Regency . This study uses a qualitative approach to data obtained more complete , in-depth , credible. So the research can systematically obtain factual and accurate picture of the factors as well as the fact that the relationship between measured using indicators appropriate to the problem under study.The conclusion of this study is there are factors that make the implementation of the products has not performed optimally; the lack of human resources at the General Hospital of Landak Regency that make the recording of products can't be maximum, the incentive to the products management officer that not doing optimally makes the lack of motivation, and the double task of products management officer on doing task the recording of products. Keywords : Performance , Regency's Property.